The Effect of Foot Orthosis Use in Reducing Pain in Patients with Plantar Fasciitis: A Meta-Analysis - Atika Febri Anggriani; Agus Kristiyanto; Setyo Sri Rahardjo (Masters Program in Public Health, 2020)
Background: Plantar fasciitis is an inflamma